Correction to: Healthcare Experiences of Underrepresented Lesbian and Bisexual Women: A Focus Group Qualitative Study by LaVaccare S, Diamant AL, Friedman J, Singh KT, Baker JA, Rodriguez TA, Cohen SR, Dary FY, and Pregler J. Health Equity 2018;2:131?138. DOI: 10.1089/heq.2017.0041. (Mary Ann Liebert, 2018)
In the 2018 volume of Health Equity (vol. 2, no.1; 131?138), the article entitled ?Healthcare Experiences of Underrepresented Lesbian and Bisexual Women: A Focus Group Qualitative Study? by LaVaccare et al. requires correction. In the originally published article, the data in Table 3 showed the ?Full sample count? for Caucasian as 13 and for African American as 8. The percentage for the ?Full sample count? of Latina showed 21.05. The data of Table 3 has been modified as shown below in gray shading. Table 3. Demographic Characteristics by Focus Group Full sample count nf=35 % African American count naa=5 % Asian-Pacific Islander count nai=7 % Latina count nl=7 % Veterans count nv=3 % 65+ count n+=13 % Race/ethnicity ?Caucasian 11 31.42 0 ? 0 ? 0 ? 1 33.00 10 77.00 ?African American 7 20.00 5 100.00 0 ? 0 ? 2 67.00 0 ? ?Asian-Pacific Islander 7 20.00 0 ? 7 100.00 0 ? 0 ? 0 ? ?Latina 8 22.80 0 ? 0 ? 7 100.00 0 ? 1 8.00 ?Nonrace 1 2.86 0 ? 0 ? 0 ? 0 ? 1 8.00 ?Other 1 2.86 0 ? 0 ? 0 ? 0 ? 1 8.00 Sexual orientation ?Lesbian 28 80.00 5 100.00 4 57.14 4 57.14 3 100.00 12 92.31 ?Bisexual 7 20.00 0 ? 3 42.86 3 42.86 0 ? 1 7.69 Age range ?18?29 8 22.86 0 ? 5 71.43 3 42.86 0 ? 0 ? ?30?39 7 20.00 1 20.00 1 14.29 3 42.86 2 66.67 0 ? ?40?49 3 8.57 1 20.00 1 14.29 1 14.29 0 ? 0 ? ?50?59 2 5.71 2 40.00 0 ? 0 ? 0 ? 0 ? ?60?64 1 2.86 1 20.00 0 ? 0 ? 0 ? 0 ? ?65+ 14 40.00 0 ? 0 ? 0 ? 1 33.33 13 100.00 Employment ?Full time 12 34.29 2 40.00 4 57.14 5 71.43 1 33.33 0 ? ?Part time 4 11.43 1 20.00 1 14.29 1 14.29 0 ? 1 7.69 ?Unemployed 4 11.43 1 20.00 2 28.57 0 ? 1 33.33 0 ? ?Retired 13 37.14 0 ? 0 ? 0 ? 1 33.33 12 93.31 ?Other 2 5.71 1 20.00 0 ? 1 14.29 0 ? 0 ? Doctor visit in the past 6 months ?Yes 29 82.86 1 20.00 6 85.71 7 100.00 2 66.67 13 100.00 Relationship status ?Not in a relationship 30 85.71 5 100.00 7 100.00 7 100.00 1 33.33 10 76.92 ?In a relationship 5 14.29 0 ? 0 ? 0 ? 2 66.67 3 23.08 Note: Percentages are estimated using the available data. The online version of the article has been corrected to reflect this change. The authors apologize for this error.